The Influence Of The Implementation Of Operational Management Functions On Employee Performance At Sushi Tei Bandar Lampung - Clara Hana Salsabila; Iskandar Ali Alam (Cita konsultindo, 2024)
This research aims to determine the effect of implementing operational management functions on employee performance at the Sushi Tei restaurant located in Bandar Lampung. It is important to understand how the implementation of operational management functions impacts employee performance, as employee performance can have a direct impact on the quality of service provided to customers and ultimately on the overall success of the business. The sampling method was total sampling with a sample of 30 Sushi Tei employees in Bandar Lampung. The data collection technique uses a questionnaire whose validity and reliability have been tested. The data analysis technique used is multiple regression, T Test, F Test, and R Squere Test with tools used by the SPSS 25 program. The results of the analysis found that together the implementation of operational management functions has an influence on employee performance of 89.7 %. Based on the results of multiple linear regression analysis, it was found that the application of operational management functions, namely planning, organizing, movement and supervision, positively influences employee performance. In other words, the better the implementation of operational management functions, the better employee performance will be in achieving business goals efficiently.